A review of oxalate poisoning in domestic animals: tolerance and performance aspects - Abdullah, Ramli; Khadijah, W.E.W.; Rahman, M.M. (2014)
Published data on oxalate poisoning in domestic animals are reviewed, with a focus on tolerance and performance. Oxalic acid is one of a number of anti-nutrients found in forage. It can bind with dietary calcium (Ca) or magnesium (Mg) to form insoluble Ca or Mg oxalate, which then may lead to low serum Ca or Mg levels as well as to renal failure because of precipitation of these salts in the kidneys. Dietary oxalate plays an important role in the formation of Ca oxalate, and a high dietary intake of Ca may decrease oxalate absorption and its subsequent urinary excretion. Oxalate-rich plants can be supplemented with other plants as forage for domestic animals, which may help to reduce the overall intake of oxalate-rich plants. Non-ruminants appear to be more sensitive to oxalate than ruminants because in the latter, rumen bacteria help to degrade oxalate. If ruminants are slowly exposed to a diet high in oxalate, the population of oxalate-degrading bacteria in the rumen increases sufficiently to prevent oxalate poisoning. However, if large quantities of oxalate-rich plants are eaten, the rumen is overwhelmed and unable to metabolize the oxalate and oxalate-poisoning results. Based on published data, we consider that <2.0% soluble oxalate would be an appropriate level to avoid oxalate poisoning in ruminants, although blood Ca level may decrease. In the case of non-ruminants, <0.5% soluble oxalate may be acceptable. However, these proposed safe levels of soluble oxalate should be regarded as preliminary. Further studies, especially long-term studies, are needed to validate and improve the recommended safe levels in animals. This review will encourage further research on the relationships between dietary oxalate, other dietary factors and renal failure in domestic animals.